Mapping of internal audit research in China: A systematic literature review and future research agenda - Saddam A. Hazaea; Jinyu Zhu; Ebrahim Mohammed Al-Matari; Nabil Ahmed Mareai Senan; Saleh F. A. Khatib; Saif Ullah (Cogent Business & Management, 2021)
The purpose of this study is to review the field of internal audit (IA) in the Chinese context and provide insights into how the literature of IA has evolved by clarifying criticism of the research published until 2020. Following the structured literature review (SLR) technique, forty-seven (47) studies were identified from two databases. The results show that the IA literature did not contribute significantly to the knowledge of IA functions in the form specified by the Institute of Internal Auditors. The study also revealed that there is more to be explored so as to fully understand the IA aspects and their impact on Chinese institutions. Descriptive research was prevalent, depending on the review of the traditional literature and the historical analysis. On the other hand, the results show that the interpretative research that relied on the case study, questionnaire, and interviews were scarce. The private sector has been little studied compared to that of the public sector. This study highlighted the real IA's practice and identified literature gaps related to the Chinese context. This study is the first comprehensive review that analyse IA research in China. It also contributes to the literature by providing a road map for future studies by interested researchers and academicians, including the Institute of Internal Auditors.
Keywords: 650; Internal audit quality; internal audit research; Web of science; Scopus; literature review; China